PERAN RASIO LIKUIDITAS SEBAGAI MEDIASI PENGARUH STRUKTUR AKTIVA TERHADAP PROFITABILITAS PERUSAHAAN TELEKOMUNIKASI DI INDONESIA - IMA ANDRIYANI (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
This study aimed to describe and analyze the structure assets on the profitability, to measure the effects of liquidity ratio as a mediationg influence structure assets on profitability. The study was conducted in the telecommunications sector in Indonesia Stock Exchange in the period of 2008 to 2012. The samples in this study were taken using purposive. The final samples in this study were 30 observations. This hypothesis was tested using path analysis. The results showed that the structure assets had no effect on the profitability and liquidity ratio was able to complete mediation influence structure assets on profitability.